Pengaruh Terapi Konseling terhadap Tingkat Depresi Pasien Melalui Pemeriksaan Mini International Neuropsychiatric Interview - Ningtiyas, Linda Kristian; Peristiowati, Yuly; Widyowati, Agustin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of counseling therapy on the level of depression in patients at the Mekarsari Community Health Center as measured by the MINI Form (Mini International Neuropsychiatric Interview). This research is a quasi-experimental quantitative research conducted using patient data based on MINI results, with a sample of 43 for the intervention group and 37 patients for the control group. The research results show that there is strong evidence showing the effectiveness of counseling therapy in reducing levels of depression. Based on research results, patients who were given counseling therapy experienced a decrease in depression levels, while the control group who were not given counseling experienced an increase in depression levels in patients in the Mekar Sari Health Center working area. The conclusion is that counseling therapy using MINI is effective in reducing the level of depression in respondents, as can be seen from the significant reduction in MINI scores after the intervention. Test results in the control group also showed a significant impact. These findings confirm the positive contribution of counseling therapy in overcoming depression, with statistical effects in both groups. Keywords: Counseling Therapy, SRQ, MINI.